Medieval narratives of accused queens - Black, Nancy B. (University Press of Florida, 2003)
''Black's study on falsely accused queens breaks new ground through its intertextual analysis of a broad selection of hitherto marginalized literary and visual narratives. The careful contextualization of her readings demonstrates admirably the hold that these figures had on the imagination of creators and audiences from across medieval Europe over a period of four centuries and down to the modern era.